Effective Communication of Bhabinkamtibmas Through Binluh Activities to Prevent Criminal Acts of Fraud at the Mojokerto Police - Kurniawan, Reski (Police Studies Review, 2024)
Fraud that can endanger society has increased in the jurisdiction of the Regional Police Mojokerto in recent years. To overcome this, preemptive efforts are very important to reduce incidents of fraud. Therefore, research is needed to evaluate performance and the Bhabinkamtibmas management system in Binluh activities. This research was conducted using a qualitative approach with descriptive analysis. Observation, documentation, and interviews were used to collect data. This study focuses on the concept of Bhabinkamtibmas, guidance and counseling, and fraud, using POAC theory, 6M management, and communication. The research results show that Bhabinkamtibmas still failed to prevent criminal acts of fraud. This is due to ongoing management problems well managed. Several things that hinder it are that Bhabinkamtibmas has multiple duties outside of its main duties. Then there is no specific material regarding criminal acts of fraud. Bhabin’s incompetence to find effective ways to communicate to prevent crime in the region Mojokerto Police law is also considered not good. Based on the research results above, the author looks for solutions experienced by Bhabinkamtibmas, the author suggests increasing vocational recruitment Bhabinkamtibmas to Bhabinkamtibmas, Bhabinkamtibmas is more intense in giving counseling regarding criminal acts of fraud, and maximizing effective communication by Bhabinkamtibmas.